Changes cytokines polymorphisms in the genes IL-2, IL -4 and IL -10 patients with pulmonary tuberculosis with chemotherapy - Butov, D (Annals of Mechnikov's Institute, 2020)
It examined 150 patients with newly diagnosed pulmonary tuberculosis (NDTL) and 30 relatively healthy donors. Areas studied genes interleukin (IL)-2 polymorphism T-330G, IL-4 – C-589T та IL-10 – G-1082A and the level of cytokines (IL- 2, IL-4 and IL-10) in venous blood were measured by ELISA method. The survey for the treatment of patients with NDTL , there was a significant increase in IL-2, and decreased IL-4, IL-10 performance, when compared with relatively healthy donors. After the two-month standard therapy showed a significant reduction in IL-2 and IL-4 content and IL-10 significantly increased. The low level of secretion of IL-4, IL-10 and high IL-2 changes significantly associated with mutant homozygotes C-589T polymorphism of the gene IL- 4, G-1082A – IL-10 and T-330G – IL-2 in patients with infiltrative tuberculosis lungs. IL-4, IL-2 and IL-10 are immune markers of treatment outcomes and can help bring out the best strategy for treating patients with NDTL. Immunogenetic factors have a protective effect in patients with NDTL is normal homozygous variant promoter regions of C-589T the gene IL-4, G-1082A – IL-10 and T-330 – GIL-2.